Chinese travellers visiting friends and relatives – A review of infectious risks. Issue 4 (July 2015) - Ma, Tara; Heywood, Anita; MacIntyre, C. Raina
Summary Background Travellers are potential vectors in the transmission of infectious diseases across international borders. Travellers visiting friends and relatives (VFR) have a particularly high risk of acquiring certain infections during travel. Chinese VFR travellers account for a substantial proportion of all travel in Western countries with high migrant populations. Methods A literature review was undertaken regarding major infectious disease risks for VFR travellers visiting China. This included an examination of the previous pandemics arising in China, the likelihood of future outbreaks in China from H5N1 and H7N9 avian influenza viruses, the potential role of travellers in disease transmission, and the special risks for VFR travellers. Results China has been the origin of several influenza pandemics in past few decades, and the origin of several emerging infectious diseases with pandemic potential, including SARS. Travel to and from China has the potential for global spread of emergent infectious diseases, as seen in the SARS outbreak in 2003. For VFR travellers, the risk of other infectious diseases may also be greater in China compared to their countries of migration, including hepatitis A and B, dengue fever, typhoid, and other diseases. Conclusions VFR travel to China may be associated with increased risk of acquiring a range of infectious diseases, and also poses a potential risk for importation of future pandemics to other countries. Chinese VFR travellers need to be cognisant of these risks and health professionals should consider educational interventions to minimise these risks.